Art and art therapy with the imprisoned re-creating identity - Gussak, David (Routledge, 2020)
Through the author's experiences, investigations and discussions with artists, art therapists and inmates from around the world, Art and Art Therapy with the Imprisoned: Re-Creating Identity comprehensively explores the efficacy, methods, and outcomes of art and art therapy within correctional settings.